The World Bank and International Monetary Fund Perspectives on the Green Economy Initiative and the Green New Deal - Santos de Araújo, Priscila; Caixeta Andrade, Daniel (Brazilian Keynesian Review, 2025)
The article addresses the need for a sustainable economic transition and the urgency to face ecological collapse, presenting the emergence of proposals for economic recovery after capitalist crises, such as the Green Economic Initiative (GEI) and the Green New Deal (GND) and their recommendations for policies inspired by Keynesianism. Through a discourse analysis of official documents, the article analyzes the extent to which international organizations such as the World Bank and the International Monetary Fund – considered crucial institutions for influencing national policies – are aligned with the perspective of the GEI and the GND and a practical reorientation of global economic policy towards a global green transition is promoted. The results show that the marginal incorporation of environmental themes was insufficient to produce a structural change in the policy recommendations of the analyzed institutions.